Transcriptome Analysis Reveals Distinct Gene Expression Profiles in Eosinophilic and Noneosinophilic Chronic Rhinosinusitis with Nasal Polyps - Wang, Weiqing (Sci Rep, 2016)
Chronic rhinosinusitis with nasal polyps (CRSwNP), one of the most prevalent chronic diseases, is characterized by persistent inflammation of sinonasal mucosa. However, the pathogenesis of CRSwNP remains unclear. Here, we performed next-generation RNA sequencing and a comprehensive bioinformatics analyses to characterize the transcriptome profiles, including mRNAs and long noncoding RNAs (lncRNAs), in patients with eosinophilic and noneosinophilic CRSwNP. A total of 1917 novel lncRNAs and 280 known lncRNAs were identified. We showed eosinophilic CRSwNP (ECRSwNP) and noneosinophilic CRSwNP (non-ECRSwNP) display distinct transcriptome profiles. We identified crucial pathways, including inflammatory, immune response and extracellular microenvironment, connected to the pathogenetic mechanism of CRSwNP. We also discovered key lncRNAs differentially expressed, including lncRNA XLOC_010280, which regulates CCL18 and eosinophilic inflammation. The qRT-PCR and in situ RNA hybridization results verified the key differentially expressed genes. The feature of distinct transcriptomes between ECRSwNP and non-ECRSwNP suggests the necessity to develop specific biomarkers and personalized therapeutic strategies. Our findings lay a solid foundation for subsequent functional studies of mRNAs and lncRNAs as diagnostic and therapeutic targets in CRSwNP by providing a candidate reservoir.